The Traditional and the Non-Traditional in the Religious Life of the Russian Federation - Kovalskaya, Kristina (Mundo Eslavo, 2013)
This article discusses a new concept of ‘traditional religions’ and other notions related to ‘tradition.’ How is public opinion being shaped, and how is decision-making and state policy towards the Russian Orthodox Church and Islam being influenced by these concepts? Since 1991, religions (in particular, the Russian Orthodox Church and Islam) have enjoyed a revival; and the Russian administration, under Yeltsin and especially under Putin, has taken a number of steps to incorporate religious establishments into the political framework of the state. We will examine these changes through the example of laws on religious liberty, and by analysing public discourse. On the one hand, the religious revival includes a number of so-called “non-traditional” religions that clearly fall under this policy. In the case of Islam, this is especially important with respect to changing Russian policies towards so-called “Wahhabism” and “religious extremism”. On the other hand, official discourse centered around “traditionality” is borrowed by the representatives of different denominations to a degree determined by public status. This phenomenon is worth studying as an incorporation of an official category into religious discourse.